A PILOT STUDY OF PIPPALYADI TAILA YONIPICHU IN THE MANAGEMENT OF KAPHAJA YONIYVAPAD (NON-SPECIFIC VAGINITIS) - Sonali R Gaikwad; Shreyes. S; Yogitha Bali M.R (AYUSHDHARA, 2020)
Background: Vaginitis is an inflammatory process involving the vagina, expanding often to the contiguous anatomical structures (cervix and vulva). Non-specific vaginitis is usually caused by an alteration (disruption) of the normal vaginal microflora, usually represented by the presence of Lactobacilli. Nonspecific vaginitis can be correlated to Kaphaja Yonivyapad based on its Lakshanas. Objectives: To evaluate the efficacy of Pippalyadi taila yoni Pichu in management of Kaphaja yoni vyapad. Design: This was a pilot study that included twenty female patients of Kaphaja yonivyapad (non specific vaginitis) from the Dept. of Prasooti tantra and Stree roga OPD of Rajiv Gandhi educational society’s Ayurvedic Medical College, Ron. Patients were administered Pippalyadi taila yonipichu for 7 days and were assessed before and after the treatment and followed up on the 14th day. Results: This pilot study showed statistically significant changes in reduction of Katishoola (p<0.001), Kandu (p<0.001), consistency of the srava (p<0.001) and Srava pramana (quantity of the discharge) (p<0.001) showing the effectiveness of Pippalyadi taila yoni Pichu in the management of Kaphaja yonivyapad. Conclusions: Pippalyadi taila yonipichu showed significant changes in the management of Kaphaja yoni Vyapad with the reduction of Katishoola, Kandu, consistency of the Srava and Srava pramana after the treatment.